Laser processing of thin-film multilayer structures: comparison between a 3D thermal model and experimental results - Naghshine, Babak B.; Kiani, Amirkianoosh (Beilstein Journal of Nanotechnology, 2017)
In this research, a numerical model is introduced for simulation of laser processing of thin film multilayer structures, to predict the temperature and ablated area for a set of laser parameters including average power and repetition rate. Different thin-films on Si substrate were processed by nanosecond Nd:YAG laser pulses and the experimental and numerical results were compared to each other. The results show that applying a thin film on the surface can completely change the temperature field and vary the shape of the heat affected zone. The findings of this paper can have many potential applications including patterning the cell growth for biomedical applications and controlling the grain size in fabrication of polycrystalline silicon (poly-Si) thin-film transistors (TFTs).
Keywords: 3D transient modelling; heat transfer; laser materials processing; nanosecond pulses; silicon; thin-film